Diseño de un texto didáctico interactivo para la asignatura de computación, del octavo año de educación básica del Colegio Técnico Agropecuario Pucará, del cantón Pucará, período lectivo 2009-2010. - Reyes Márquez, María Marlene (2013)
It is not easy for teachers to answer the question of how to teach to pique the interest of students and through active participation of the same guide them towards meaningful learning.